Monotheism and dualism in Nahmanides' Kabbalistic thought: formation, volte-face and evolution - Yiśraʾeli, ʿOded (Journal of Jewish studies, 2019)
Nahmanides (Rabbi Moses ben Nahman, 1194-1270) was one of the prominent early Kabbalists in the thirteenth century in Catalonia. This article examines the way in which Nahmanides treats the deepest theological problem regarding the notion of the sefirot -- the issue of plurality within the godhead. Nahmanides embraced the Kabbalistic doctrine of the sefirot, but he was committed to the principle of divine unity. Analysis of the changes and developments his thought underwent during his lifetime sheds light on the protracted, complex process this involved. While early on in his career he firmly espoused a monotheism that 'contained' the sefirot, in his latter days he was compelled for historical reasons to redefine the relationship between God and the sefirot. To this end he disseminated a clarificatory passage from Eretz Israel that he sought to append to the commentary. In this appendix he explained the principle of the sefirot in a new and more moderate theological way. The article focuses on this biographical change and tries to analyse it thoroughly.